MODAL INTELEKTUAL DAN KINERJA PERUSAHAAN STUDI EMPIRIS DI BURSA EFEK INDONESIA - Shadrina Hazmi (Ma Chung Press, 2018)
This study aims to examine the effect of intellectual capital on company performance and examine the differences in the influence of intellectual capital on company performance in the service sector and manufacturing. The sample in this study is the company in the manufacturing sector and service sector with the 2011-2015 research period. Intellectual capital is measured using value added intellectual coefficient (VAIC) and company performance is measured by return on assets (ROA). The results showed that intellectual capital had a significant positive effect on company performance and the effect of intellectual capital on corporate performance was stronger in the service sector than in the manufacturing sector.